Spectral Analysis Lectures given at a Summer School of the Centro Internazionale Matematico Estivo (C.I.M.E.) held in Varenna (Como), Italy, August 24-September 2, 1973 - Cecconi, Jaures (C.I.M.E. Summer Schools, 2011)
G. Bottaro: Quelques résultats d'analyse spectrale pour des opérateurs différentiels à coefficients constants sur des domaines non bornés.- L. Gårding: Eigenfuction expansions.- C. Goulaouic: Valeurs propres de problèmes aux limites irréguliers: applications.- G. Grubb: Essential spectra of elliptic systems on compact manifolds.- J.Cl. Guillot: Quelques résultats récents en Scattering.- N. Schechter: Theory of perturbations of partial differential operators.- C.H. Wilcox: Spectral analysis of the Laplacian with a discontinuous coefficient.